Implementation of the ”7 Habits of Great Indonesian Children” in Elementary Student Character Development - Ayu Lestari; Yusrizal Yusrizal; Fira Astika Wanhar (Institut of Shanti Bhuana, 2026)
This study aims to describe the implementation of the 7 Habits of Great Indonesian Children Program in shaping the character of students at PAB 29 Manunggal Private Elementary School. The study used a qualitative descriptive approach and was conducted in November 2025. The research subjects consisted of 1 principal, 1 fifth-grade teacher, and 3 fifth-grade students. Data were collected through interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman interactive model through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the program implementation has been running quite well through systematic planning, adequate support facilities, and the integration of character values ​into routine school activities. The implementation of the program is seen in morning prayer activities, literacy, class duty, group work, and Clean Friday. The implementation of the program is also seen in the development of discipline, responsibility, independence, cooperation, honesty, creativity, and self-care in students. Program evaluation is carried out periodically through teacher meetings and observations of changes in student behavior. Overall, this program has a positive impact on the formation of student character and is supported by an orderly and clean school atmosphere, as well as a harmonious relationship between teachers and students.